A prospective, multicenter, single-arm clinical trial cohort to evaluate the safety and effectiveness of a novel stent graft system (WeFlow-JAAA) for the treatment of juxtarenal abdominal aortic aneurysm: A study protocol - Gao, Jiang-Ping; Zhang, Hong-Peng; Jia, Xin; Xiong, Jiang; Ma, Xiao-Hui; Wang, Li-Jun; Zhang, Min-Hong; Xu, Yong-Le; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Introduction Juxtarenal abdominal aortic aneurysms (JRAAAs) are challenging to cure by traditional endovascular aortic repair (EVAR). Due to the inherent disadvantages of the customized fenestrated and/or branched aortic endografts (such as delayed cycles with a risk of aneurysm rupture, unavailable in emergency or confine operations), several off-the-shelf devices have been developed for the treatment of JRAAA. However, these devices being used in clinical trials have been proven to have a non-negligible risk of reintervention and inadequate anatomic applicability. We have developed a new off-the-shelf aortic endograft system (WeFlow-JAAA) with a mixed design of inner branches and modified fenestrations. The purpose of this cohort study is to assess the safety and effectiveness of the innovative aortic endograft system. Methods and analysis This is a prospective, multicenter, single-armed clinical trial cohort study. The enrolment will take place in 29 centers in China, and 106 adult patients with JRAAA will be enrolled in total. Clinical information and CT angiography (CTA) images will be collected and recorded. Patients will be followed up for 5 years. The primary safety endpoint is the rate of no major adverse event within 30 days after index EVAR. The primary efficacy endpoint is the rate of immediate technical success and no JRAAA-related reintervention within 12 months after the procedure.